2015
DOI: 10.1186/s12906-016-1027-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Myofascial-meridian Release Acupuncture (MMRA) for chronic neck pain: a study protocol for randomized, patient- and assessor-blinded, sham controlled trial

Abstract: BackgroundThe purpose of this study is to evaluate the efficacy and safety of myofascial-meridian release acupuncture (MMRA) in the treatment of chronic neck pain compared with sham acupuncture.Methods/designA protocol for a randomized, patient- and assessor-blinded, sham controlled parallel trial is presented. Seventy-four participants with a ≥3 month history of neck pain and a score of ≥4 on the 11-point pain intensity numerical rating scale (PI-NRS) will be randomly assigned to the MMRA group (n = 37) or sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Chimsband was developed to normalise the bioelectrical current by attaching to the acupoints or on the Ashi points, which are painful areas that usually show abnormally high or low dermal biocurrents. Previous case studies reported their clinical effectiveness in reducing chronic pain and other symptoms from depressive disorders and sleep disorders [ 13 , 16 ]. However, the mechanism behind the clinical results has not yet been proven in the experimental setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimsband was developed to normalise the bioelectrical current by attaching to the acupoints or on the Ashi points, which are painful areas that usually show abnormally high or low dermal biocurrents. Previous case studies reported their clinical effectiveness in reducing chronic pain and other symptoms from depressive disorders and sleep disorders [ 13 , 16 ]. However, the mechanism behind the clinical results has not yet been proven in the experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…If the score exceeds 40 points on screening, the participant will be enrolled in the study. Visit 11 will be at visit 1 + 2 weeks + 6-window days (last Chimsband attachment or ICT + 6-window days), as first follow-up date [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…For inducing Deqi sensation, we will rotate the needles left and right 3 to 5 times and then keep the needles in place for 15 minutes. [ 17 ] After the needle has been removed, the treatment area will be disinfected using cotton saturated with 78% alcohol. All manual acupuncture treatments will be performed by Korean Medicine doctors who have had manual acupuncture treatment experience for more than 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…The PI-NRS is an 11-point Likert scale that assesses the severity of neck pain perceived by a patient. This scale is widely used for pain studies [ 40 ], including neck pain [ 41 ]. A patient is asked to pick one value from 0 (not painful) to 10 (most painful) based on the pain level for the past 24 hours.…”
Section: Methodsmentioning
confidence: 99%